HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG KANKER SERVIKS TERHADAP KEBERSIHAN PERSONAL HYGIENE PADA REMAJA DI SMA SENEB TONASA - Sri Ayu Nata (Jurnal Kesehatan Amanah, 2019)
The prevalence of cervical cancer in Indonesia is increasing, reaching 1.79 per 1000 population. According to the Global Cancer Observatory 2018 data, cervical cancer is the second most common cancer among women in Indonesia, with a prevalence of 32,469 cases or 9.3% of the total cases. This issue arises because many adolescents do not maintain proper personal hygiene during menstruation. Women who lack proper personal hygiene have a 19,386 times greater risk of developing cervical cancer compared to those with good personal hygiene. Cervical cancer prevention in adolescents is carried out by maintaining genital hygiene properly. The study aims to determine the relationship between knowledge about cervical cancer and genital personal hygiene behavior among adolescents. Cervical cancer is the growth of abnormal cells in the cervix. Genital personal hygiene behavior involves maintaining individual cleanliness and health. The research design is correlational with a cross-sectional approach. The study population comprises 392 adolescent girls, with a sample of 195 adolescent girls selected using purposive sampling technique. The validity test using the Pearson product-moment showed all results to be valid with a P value < 0.05. The reliability test for the knowledge variable is 0.623, and for the behavior variable, the r value is 0.865. The study results show that most adolescents have fairly good knowledge (41.5%) but poor hygiene behavior (54.4%), with a Chi-Square P value = 0.000. There is a relationship between knowledge about cervical cancer and genital personal hygiene behavior among adolescents. It is recommended for Selabatu Health Center to conduct outreach on cervical cancer to improve adolescents' personal hygiene practices.